Application of the Adverse Outcome Pathway Framework to Risk Assessment for Predicting Carcinogenicity of Chemicals - Kang, Doo Seok (J Cancer Prev, 2018)
As industry develops in modern society, many chemicals are being used. The safety of chemicals is an important issue because humans are constantly exposed to chemicals throughout their daily life. Through a risk assessment, the hazardous human effects of chemicals can be identified. Recently, the adverse outcome pathway (AOP) framework has been used to predict the adverse effects of chemicals. As a conceptual framework for organizing existing biological knowledge, the AOP consists of a molecular initiating event, key events, and an adverse outcome. These independent elements represent biological responses and are connected by key event relationships. This AOP framework provides intuitive hazard identification that can be helpful for carcinogenic risk assessment of chemicals. In this review, we introduce the application of the AOP framework to risk assessment for predicting carcinogenicity of chemicals and illustrate the utility of this approach for cancer prevention.